Etiology and severity of diarrheal diseases in infants at the semiarid region of Brazil: A case-control study. - Aldo A M Lima; Domingos B Oliveira; Josiane S Quetz; Alexandre Havt; Mara M G Prata; Ila F N Lima; Alberto M Soares; José Q Filho; Noélia L Lima; Pedro H Q S Medeiros; Ana K S Santos; Herlice N Veras; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Diarrheal diseases are an important cause of morbidity and mortality among children in developing countries. We aimed to study the etiology and severity of diarrhea in children living in the low-income semiarid region of Brazil. METHODOLOGY:This is a cross-sectional, age-matched case-control study of diarrhea in children aged 2-36 months from six cities in Brazil's semiarid region. Clinical, epidemiological, and anthropometric data were matched with fecal samples collected for the identification of enteropathogens. RESULTS:We enrolled 1,200 children, 596 cases and 604 controls. By univariate analysis, eight enteropathogens were associated with diarrhea: Norovirus GII (OR 5.08, 95% CI 2.10, 12.30), Adenovirus (OR 3.79, 95% CI 1.41, 10.23), typical enteropathogenic Escherichia coli (tEPEC), (OR 3.28, 95% CI 1.39, 7.73), enterotoxigenic E. coli (ETEC LT and ST producing toxins), (OR 2.58, 95% CI 0.99, 6.69), rotavirus (OR 1.91, 95% CI 1.20, 3.02), shiga toxin-producing E. coli (STEC; OR 1.77, 95% CI 1.16, 2.69), enteroaggregative E. coli (EAEC), (OR 1.45, 95% CI 1.16, 1.83) and Giardia spp. (OR 1.39, 95% CI 1.05, 1.84). By logistic regression of all enteropathogens, the best predictors of diarrhea were norovirus, adenovirus, rotavirus, STEC, Giardia spp. and EAEC. A high diarrhea severity score was associated with EAEC. CONCLUSIONS:Six enteropathogens: Norovirus, Adenovirus, Rotavirus, STEC, Giardia spp., and EAEC were associated with diarrhea in children from Brazil's semiarid region. EAEC was associated with increased diarrhea severity.